2021
DOI: 10.18502/ijph.v50i12.7941
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of SLC2A3 Expression on Cisplatin Resistance of Colorectal Cancer Cells

Abstract: Background: To study the molecular mechanism of cisplatin chemotherapy resistance in colorectal cancer cells and to explore the effect of miRNA in regulating the expression of glucose transporter 3 (SLC2A3) and the proliferation and migration of colon cancer cells. Methods: All samples were obtained from the People’s Hospital of Wuhai, Wuhai, China between June 2019 and June 2020. Real-time quantitative PCR (qRT-PCR) was carried out to check the expression of miR-103a in these cell lines. Western blottin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…54 SLC2A3 exerts multiple biological functions in different cancers, including tumor EMT, ferroptosis, glycolytic reprogramming, drug resistance and immunity. [55][56][57][58][59] Immune cell infiltration analysis showed that SLC11A1 and SLC2A3 expression was positively correlated with the infiltration levels of neutrophils, macrophages, dendritic cells, CD4+ T cells and CD8+ T cells. Moreover, the higher the expression levels of SLC11A1 and SLC2A3, the lower the tumor purity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 SLC2A3 exerts multiple biological functions in different cancers, including tumor EMT, ferroptosis, glycolytic reprogramming, drug resistance and immunity. [55][56][57][58][59] Immune cell infiltration analysis showed that SLC11A1 and SLC2A3 expression was positively correlated with the infiltration levels of neutrophils, macrophages, dendritic cells, CD4+ T cells and CD8+ T cells. Moreover, the higher the expression levels of SLC11A1 and SLC2A3, the lower the tumor purity.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, SLC11A1 not only predicts the prognosis of colorectal cancer and hepatocellular carcinoma 52,53 but also serves as a stratification indicator for immunotherapy or chemotherapy in glioma patients 54 . SLC2A3 exerts multiple biological functions in different cancers, including tumor EMT, ferroptosis, glycolytic reprogramming, drug resistance and immunity 55–59 . Immune cell infiltration analysis showed that SLC11A1 and SLC2A3 expression was positively correlated with the infiltration levels of neutrophils, macrophages, dendritic cells, CD4+ T cells and CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%